Teacher's Ethics, Skills, and Duties in the Lesson (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
In the dynamic landscape of education, this article probes into the  multifaceted responsibilities of educators within the classroom, emphasizing the integral  triad of ethics, skills, and duties. It critically examines the ethical considerations intrinsic  to effective teaching, underlining the significance of maintaining professional integrity  and confidentiality. The article navigates through the essential skills requisite for  impactful teaching, delving into the nuances of communication, adaptability, and pedagogical  versatility. Furthermore, it sheds light on the diverse duties educators undertake, ranging from meticulous classroom management to the art of providing constructive feedback. Rich with practical examples, this piece offers a comprehensive exploration of the pivotal role teachers play in shaping the educational experience, ensuring an engaging and ethically grounded learning environment